A new species of clearwing moth (Lepidoptera: Sesiidae: Osminiini) from Peninsular Malaysia, exhibiting bee-like morphology and behaviour - Skowron, Marta A.; Munisamy, Badmanathan; Hamid, Suhaila Binti Ab.; Węgrzyn, Grzegorz (Zootaxa, 2015)
A new species of Sesiidae, tribe Osminiini from Peninsular Malaysia, Heterosphecia pahangensis Skowron, displaying numerous bee-mimicking features, is described. DNA barcodes showed significant differences with related taxa. However, the paucity of Sesiidae barcodes from Southeast Asia prevents meaningful taxonomic comparisons. The closest match out of published data on Sesiidae barcodes is Heterosphecia bantanakai, Arita & Gorbunov (2000a) from the tribe Osminiini, which has 9.98% sequence divergence from Heterosphecia pahangensis. Photographs of the moth in its natural habitat are shown. Behavioural aspects, such as mud-puddling and mode of flight, are described and presented in a video.